The value relevance of SAM's corporate sustainability ranking and GRI sustainability reporting in the European stock markets. (17th September 2014) - Kaspereit, Thomas; Lopatta, Kerstin
Abstract : This paper investigates whether relative corporate sustainability as measured by the SAM sustainability ranking and sustainability reporting in terms of Global Reporting Initiative (GRI) application levels are associated with a higher market valuation. We conduct a value relevance study for the 600 largest European companies with the Feltham and Ohlson valuation model as a reference point. Our results indicate that for the observation period 2001 to 2011, the association between corporate sustainability and market value is positive. The empirical evidence of a positive relationship between GRI reporting and market value is statistically significant in some but not all of the model specifications. We find no evidence of interaction between the value relevance of corporate sustainability and sustainability reporting, nor do we find any positive effect of external assurance on the capital market perception of GRI application levels. Our results support the notion that conducting business in accordance with ethical norms is also a shareholder value‐increasing business strategy. However, it is not possible to verify the information given in sustainability reports through external assurance.